2011
DOI: 10.1093/brain/awq369
|View full text |Cite
|
Sign up to set email alerts
|

Left inferior frontal cortex and syntax: function, structure and behaviour in patients with left hemisphere damage

Abstract: For the past 150 years, neurobiological models of language have debated the role of key brain regions in language function. One consistently debated set of issues concern the role of the left inferior frontal gyrus in syntactic processing. Here we combine measures of functional activity, grey matter integrity and performance in patients with left hemisphere damage and healthy participants to ask whether the left inferior frontal gyrus is essential for syntactic processing. In a functional neuroimaging study, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
184
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(206 citation statements)
references
References 92 publications
(121 reference statements)
16
184
4
2
Order By: Relevance
“…A large body of studies of L1 using English as a test language found enhanced activity in Broca's area (that is, left BA 44 and BA 45 extending to BA 47), suggesting that this area is activated by syntactic manipulations and task demands 33 . However, it has been also postulated that BA 47, usually combined with BA 45, supports the retrieval of semantic information and the processing of semantic relationships between words in sentences 34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of studies of L1 using English as a test language found enhanced activity in Broca's area (that is, left BA 44 and BA 45 extending to BA 47), suggesting that this area is activated by syntactic manipulations and task demands 33 . However, it has been also postulated that BA 47, usually combined with BA 45, supports the retrieval of semantic information and the processing of semantic relationships between words in sentences 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that BA 47/45 is connected to the temporal lobe via the ECFS, as a ventral pathway, supporting the processing of semantic information 37 and syntactically simple sentences 33 . As mentioned above, the task of BRAN in L2 may be related to processing semantic information, as well as building up a sentence structure.…”
Section: Discussionmentioning
confidence: 99%
“…A third position attributes both core language functions to part of Broca's region (though not necessarily specifically to syntax), as well a multiple demand system characteristics to other parts of Broca's region [42]. In the MUC framework [5 ] Broca's region is not language-specific, but realizes its language-relevant unification function in connection to language-relevant areas in temporal and inferior parietal cortex that support the storage of different types of linguistic knowledge [43 ]. Recently, a similar network view has been advocated by .…”
Section: Current Opinion In Neurobiologymentioning
confidence: 99%
“…Recently, the key role of the left inferior frontal gyrus (Broca's area) in syntactic processing has been questioned on the grounds that studies typically involve task and stimulus demands may activate brain regions that overlap with those involved in linguistic computations, making it difficult to differentiate between linguistic and non-linguistic processes (Tyler et al 2011). As reviewed by Stowe, Haverkort & Zwarts (2005), recent neuroimaging evidence show that the left inferior frontal gyrus plays some role in comprehending sentences when processing is more difficult, but combined with the simple sentence results, they suggest that the left inferior frontal gyrus is not exclusively dedicated for syntactic processing.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 99%
“…As reviewed by Stowe, Haverkort & Zwarts (2005), recent neuroimaging evidence show that the left inferior frontal gyrus plays some role in comprehending sentences when processing is more difficult, but combined with the simple sentence results, they suggest that the left inferior frontal gyrus is not exclusively dedicated for syntactic processing. More recently, in a functional neuroimaging study of the linguistic performance in patients with left hemisphere damage and healthy participants, Tyler et al (2011) have found that the left inferior frontal gyrus may not itself be specialized for syntactic processing, but plays an essential role in the neural network that carries out syntactic computations. This net involves a variety of brain areas co-activated with the left inferior frontal gyrus, including the right inferior frontal gyrus, bilateral superior temporal gyrus, left middle temporal gyrus and a more posterior temporoparietal cluster including left inferior parietal lobule, left angular gyrus and left supramarginal gyrus.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 99%